Integrated Dynamics of Kinetic and Kinematic Control in Hand Grip Function: Postural and Visual Effects - Althoff, Bernardo Figueira; Nakamoto, João Carlos; Saito, Mateus; Sorrenti, Luiz; Escudero, Ricardo Boso; Wataya, Erick Yoshio (Revista Brasileira de Ortopedia, 2025)
To interpret, with objective data, the kinetic and kinematic control of gripper function associated with visual and stereognostic control.In total, 34 young participants, without previous hand diseases or traumas, underwent pinch grip tasks with the wrist in a neutral position and at 45° of flexion. The tasks were repeated three times.The movement difference in the neutral and 45° of flexion postures presented a significant correlation with the pulp-to-pulp distance variables (r values from 0.38 to 0.41; p < 0.05). The strength difference in the neutral and 45° of flexion postures, with or without visual feedback, also showed a significant correlation (r values from 0.45 to 0.47; p < 0.01). The movement and strength differences presented a significant correlation in the neutral posture without visual feedback (r = 0.77; p < 0.001) and in the flexed posture with visual feedback (r = 0.48; p = 0.004).Visual feedback and wrist posture influence strength and movement control in gripping function in healthy adults. These findings reinforce the interdependence of control mechanisms in hand function. Postural adjustments and proprioception enhancement can optimize functional recovery, with implications for the development of specific tests and their application in actual clinical settings.
Keywords: feedback; movement; wrist